2023
DOI: 10.1111/jcmm.17787
|View full text |Cite
|
Sign up to set email alerts
|

Integration of molecular docking, molecular dynamics and network pharmacology to explore the multi‐target pharmacology of fenugreek against diabetes

Abstract: Fenugreek is an ancient herb that has been used for centuries to treat diabetes. However, how the fenugreek‐derived chemical compounds work in treating diabetes remains unclarified. Herein, we integrate molecular docking and network pharmacology to elucidate the active constituents and potential mechanisms of fenugreek against diabetes. First, 19 active compounds from fenugreek and 71 key diabetes‐related targets were identified through network pharmacology analysis. Then, molecular docking and simulations res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…ADMET analysis is an important tool in drug discovery [ 19 , 20 ]. We performed ADMET analysis on compound P3 using the ADMET-AI platform, and the results showed that compound P3 has excellent pharmacokinetic properties.…”
Section: Resultsmentioning
confidence: 99%
“…ADMET analysis is an important tool in drug discovery [ 19 , 20 ]. We performed ADMET analysis on compound P3 using the ADMET-AI platform, and the results showed that compound P3 has excellent pharmacokinetic properties.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the 'Network Analyzer' tool was used to analyze the topological properties. 18,19 The primary signaling pathways implicated in viral respiratory illness were investigated using the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis and Wikipathways. 20…”
Section: Collection and Screening Of Target Proteins Related To Viral...mentioning
confidence: 99%
“…22 In recent times, there has been extensive investigation and research on the potential of fenugreek in managing diabetes and its complications due to the alarming surge in diabetes patients worldwide. [23][24][25] This study aims to investigate the therapeutic effect of fenugreek on ED in diabetes and explore the underlying mechanism. The fenugreek extract was prepared and its chemical composition was analyzed using ultrahigh-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MS).…”
Section: Introductionmentioning
confidence: 99%
“…22 In recent times, there has been extensive investigation and research on the potential of fenugreek in managing diabetes and its complications due to the alarming surge in diabetes patients worldwide. 23–25…”
Section: Introductionmentioning
confidence: 99%